Locus de controle e reação a frustração - Coelho, Cristina Lucia Maia (1984)
The purpose of the present study 19 to analyse the relationship between Rotter's Learning theory in terms of 'locus of. control' and Rosenzweig's Theory of Frustration. The review of the existing frustration theories resulted on a model which allowed the evaluation of 'social perception' interference upon the reaction to frustration we examined three of the possible theoretic91 explanations to determine the differences of perception of the 'locus of control': the first one was examined in terms of the learning theory the second one, in terms of character organization and the third one in terms of temperament factors. We also presented a review of the experimental attempts and confirmations concerning the construct 'locus of control' and the reaction to' frustration. The empírical verification of the proposed model consisted of a pilot research to prove the relatlonship between the 'locus of control' variable and the ·tolerance to frustration (under certain aspects). Paralelly, we were able to examine the role of the variable - university education. We studied a group of university students and the results indicated that the interns presented a move mature level of tolerance to frustration. The students persistance in attaining goals and ability to initiative before frustrating sltuat1.ons revealed this higher level of maturity. Despite the 'locus of control', and concerning the University career education students resulted more intrapunitive than others. The analysis of the influence of the kind of frustrating situation, finally showed that the circunstances involving the 'threatening of the ego' led to an emotional discharge of the gul1ty type In detriment to initiative. In addition the extrapunitive reections were more moticiable during those situations in which the subject had its goals blockaded.